2004
DOI: 10.1001/archotol.130.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Events Associated With Impaired Olfactory Function

Abstract: To evaluate the risk of olfactory-related hazardous events in patients with impaired olfactory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
188
2
16

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(214 citation statements)
references
References 16 publications
3
188
2
16
Order By: Relevance
“…In a recent study of Drummond et al (41) that investigated patients after traumatic brain injury and resulting changes in their ability to smell, olfactory dysfunction was associated with significant impact on a range of activities and social roles, like work, relationship, personal hygiene and leisure. Santos et al demonstrated, that individuals with an olfactory disorder have at least twice the risk of being involved in potentially life-threatening situations (42). The latter includes detection of natural gas leakages or smoke and consuming of spoiled foods.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of Drummond et al (41) that investigated patients after traumatic brain injury and resulting changes in their ability to smell, olfactory dysfunction was associated with significant impact on a range of activities and social roles, like work, relationship, personal hygiene and leisure. Santos et al demonstrated, that individuals with an olfactory disorder have at least twice the risk of being involved in potentially life-threatening situations (42). The latter includes detection of natural gas leakages or smoke and consuming of spoiled foods.…”
Section: Discussionmentioning
confidence: 99%
“…Also, smelling can modulate appetite, dietary behaviors, and nutritional status (Duffy et al, 1995;Aschenbrenner et al, 2008;Seo & Hummel, 2009). Moreover, olfaction warns of possible microbial threat (e.g., from feces, vomit, or organic decay), evoking disgust , and of nonmicrobial hazards including gas leaks, smoke, and toxic materials, eliciting fear (Cain & Turk, 1985;Cain et al, 1987;Miwa et al, 2001;Santos et al, 2004). We therefore tested the ability of the last-mentioned subjects to detect, describe and judge the smell of dimethyl-disulfide (DMDS) ), a byproduct of the decomposition of various foods which has a characteristic smell of rotten cabbage and is largely responsible for the smell of different decaying or putrefying foods including milk (van Aardt et al, 2005).…”
Section: Are These Findings Relevant For Everyday Life?mentioning
confidence: 99%
“…However, olfaction is a critical physiologic function in humans: normal perception is fundamental for detection of many warning signals of life-threatening situations, such as smoke, spoiled food, dangerous chemicals, gas leaks, etc. : in some studies a relation was observed between the degree of olfactory loss and the risk of hazardous events [1,2]. Furthermore, nutritional status and many other topics related to the quality of life may be affected by the impairment of olfactory function [3], and loss of smell is accompanied by an increased risk of depression [4].…”
Section: Introductionmentioning
confidence: 99%